Use of alternative sweeteners in ice cream - Polishchuk, Galyna; Bass, Oksana (My University, 2021)
The article is devoted to research aimed at improving the technology of ice cream through the use of sugar substitutes and their compositions that exhibit functional and technological properties and improve the quality of the finished product. The feasibility of using starch syrup and polyols for the formation of recommended organoleptic, physical and chemical characteristics of ice cream, and their stabilization during the guaranteed period of storage is scientifically substantiated
Keywords: cryoscopic temperature; ice cream; polyols; кріоскопічна температура; морозиво; поліоли; кафедра технології молока і молочних продуктів